The use of Artemia sp. or mysids as food source for hatchlings of the cuttlefish (Sepia officinalis L.); effects on growth and survival throughout the life cycle - Domingues, Pedro M. (2018)
Two experiments were conducted to determine the effects of Artemia sp. or mysids on growth and survival of S. offıcinalis hatchlings, and their effect throughout the life cycle. For experiment I, for the first 20 days, one group was fed adult Artemia sp. and the other was fed mysid shrimp (Paramysis nouvelli). Eggs laid by females in both groups were counted and weighed, and hatchlings were weighed, to determine differences in both groups. For experiment II, during the first 10 days, one group was fed Artemia sp. and the other was fed mysids (P. nouveli). After the period of differentiated feeding, the 2 groups in experiment I were fed grass shrimp (Paleomonetes varians) to 70 days old, and dead crabs (Carcinus maenas) afterwards. Cuttlefish in experiment II were fed grass shrimp from day 10 until the end of the experiment. For both experiments, hatchlings fed mysids grew significantly bigger (p < 0.01) and survival was higher. For experiment I, eggs laid by females fed mysids and the hatchlings born from these eggs were bigger (p < 0.001) compared to the group fed Artemia sp. initially. Individual fecundity was slightly higher for females in the group fed Artemia sp. (163 eggs female−1) than for the group fed mysids (144 eggs female−1). Egg laying started at the age of 125 days and lasted 45 days in both groups. Time between first egg laying day and first hatchlings to be born was 21 days. The last female to die (after spawning) in both groups was 167 days (less than 6 months old).